Fatal H1N1-Related Acute Necrotizing Encephalopathy in an Adult - Yu-Jin Lee; D. Scott Smith; Vivek A. Rao; Robert D. Siegel; Jon Kosek; Carol A. Glaser; Alexander C. Flint (Case Reports in Critical Care)
Acute necrotizing encephalopathy (ANE) is a severe neurological complication of influenza infection, including H1N1 influenza. Many cases of ANE have been reported in the pediatric literature, but very few cases have been described in adults. The cause of ANE remains unknown—the influenza virus is not known to be neurotropic, and evidence of direct viral involvement of the central nervous system (CNS) has not been demonstrated in the limited cases of ANE in which pathological specimens have been obtained. Here we report a fatal case of ANE from H1N1 influenza infection in an adult. Neuroimaging and postmortem analysis both showed widespread brain edema, necrosis, and hemorrhage, but molecular studies and postmortem pathology revealed no evidence of direct viral involvement of the CNS. This case of fatal ANE in an adult is consistent with the hypothesis generated from pediatric cases that the host immune response, and not direct viral invasion of the CNS, is responsible for pathogenesis of ANE.